PEMAHAMAN GURU TERHADAP NILAI AMANAH DAN KEADILAN DALAM PEMBELAJARAN HADIS BAB 18 KITAB AT-TIJAN FI SYU'AB AL-IMAN DI MA AL ISLAM JAMSAREN SURAKARTA - Maajida, Dini Luthfiyya; A’yun, Khosyi’ah Qurrota; Ash Sholihah, Hanifah; Anwar, Aqilla Fadia Hayya; Abbas, Ngatmin (MAMBA'UL 'ULUM, 2025)
This study aims to analyze in depth the teacher’s understanding of the values of trustworthiness (amanah) and justice (‘adl) in teaching Hadith Chapter 18 of the At-Tijan fi Syu’ab al-Iman at MA Al Islam Jamsaren Surakarta. The research questions focus on how teachers comprehend, implement, and internalize these moral values within the Hadith learning process. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews with Hadith teachers, classroom observations, and documentation studies, then analyzed thematically through the stages of data reduction, presentation, and conclusion drawing. The findings reveal that the teacher demonstrates a comprehensive understanding of trustworthiness and justice as fundamental moral and spiritual principles in Islamic education. Amanah is perceived as a manifestation of faith and responsibility, while ‘adl is understood as maintaining balance and fairness in actions and decisions. These values are integrated through contextual learning and exemplary behavior, reinforced by a religious and disciplined school culture. The study concludes that Hadith learning functions not merely as a transfer of religious knowledge but as a transformative process for building Islamic character and moral integrity. The research contributes theoretically to the development of Hadith-based value learning models and provides practical implications for strengthening character education in Islamic schools (madrasah). The implication is that Hadith learning emphasizing the values of trustworthiness and justice should be contextually adapted to ensure its relevance to the moral challenges faced by the modern generation.